(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Celebrity endorsement has been established as one of the most accepted tools of advertising in modern era. Its widely accepted use and benefits prove that every company must take into consideration this tool while framing their strategies to get competitive advantage in a market place because it has become a trend and perceived as a winning formula for product marketing and brand building. This paper is a review paper that deals with analytical review of the existing literature to understand the factors effecting celebrity endorsement and its impact. Further an attempt has been made to present it in a synoptic way with the help of review based models. Various determinants of celebrity endorsement were bifurcated in four major factors Celebrity related, Product related, Customer related and other strategic factor. Several Studies have been conducted to investigate the effectiveness of Celebrity advertisement yet the magnitude of the impact of celebrity endorsement remains under the purview of gray spectacles. Hence, this paper is an effort to analyze the impact of celebrity endorsements with the help of a model.